Pengembangan E- Comic Education pada Mata Pelajaran Ilmu Pengetahuan Alam Materi Gaya dan Manfaatnya - Hanifah, Hindun; Maslikhah, Maslikhah (Mitra PGMI: Jurnal Kependidikan MI, 2022)
The purpose of the study was to determine the need for developing e- comic education learning media to improve cognitive learning outcomes for fourth grade students of MI NU Tsamrotul Wathon. The type of this research is Research and Development  with ADDIE model. Data collection techniques used questionnaires, and tests. The limited scale test was carried out with 10 students and the broad scale test was carried out with 30 students. The results showed that: the results of the validation of the eligibility criteria were based on the validation media experts, material experts and practitioners. Eligibility criteria for displaying writing are 62.5% (fair enough), image eligibility 72.5% (fair enough), e-comic education media function is 91.6% (very feasible), e-comic education media benefits are 87.5%. The eligibility criteria for the content aspect are 83.92% (very feasible), the feasibility on the construction aspect is 68.75% (adequate) and the feasibility of the language aspect is 60% (fair enough). The results of the development of e-comic education media are very effective in influencing students cognitive learning outcomes as indicated by the increase in cognitive learning outcomes with α < 0,05 its mean 0.00 < 0.05. The gain test of 0.467 is in the medium category.